Human Rights Studies: A Systematic Literature Review (SLR) - Melani, Yeni; Salahudin, Salahudin; Firdaus, Muhammad; Sumitro, Sumitro (CV. Rayyan Dwi Bharata, 2024)
This research aims to understand and analyse developments in the study of human rights.The research involves the collection and analysis of data from various sources and literature on human rights. And not limited to academic journals, research articles, reports of international organizations and legal documents. The research method applied to this research is systematic literature review using 145 scientific articles sourced from data scopus. The results of the research reveal that this research seeks to produce a comprehensive and in-depth picture of how human rights studies have evolved and changed over time. The limitation of this research is that the articles used are only sourced from scopus databases so the research findings cannot describe comprehensively about human rights in the world. Further research needs to use scientific articles that come from other reputable international databases, such as the Web of Science and Dimensionds Scholars.